Nouveaux hétérocycles d'isatine : Applications biologiques et étude de l'effet inhibiteur de corrosion dans différents milieux acides - Kharbach Yassine (Université Sidi Mohamed Ben Abdellah, Faculté des Sciences et Techniques - Saïs -, Fès, 2017)
The topic of this thesis brings avantages to complete our searches within Applied Chemistry Laboratory (LCA) at the Faculty of Sciences and Techniques of Fez, concerning the synthesis and the application of 5-bromo-1H-indole-2,3-dione. The first chapter, will give a bibliographical reminder concerning the synthesis and the reactivity of the derivatives containing the 1H-indole-2,3-dione system. In the second chapter, the synthesis was described by a simple and effective method to prepare new derivatives of 5-bromo-isatin by performing alkylation reactions under the conditions of phase transfer catalysis (PTC). The structures of the different products obtained were determined by (1H NMR, 13C NMR and X-ray crystallographic study). The third chapter reports the synthesis of new 5-bromo isatin derivatives by 1,3-dipolar cycloaddition reactions. This study allowed us to confirm the stability of certain 1,4 and 1,5 substituted regioisomers, using the DFT / B3LYP / 6-31G method. In the fourth chapter, we tested the application of certain compounds on corrosion of mild steel in hydrochloric and sulfuric acid, using gravimetric, electrochemical and surface analysis methods (SEM, XPS). These products have shown a very high efficiency in terms of corrosion inhibition. The last chapter has been devoted to the study of the biological activity of N-alkylisatins, these compounds have a vasodilatory effect which induces a drop in LVM perfusion pressure, so they exhibit very important antibacterial properties towards the studied microorganisms.
Keywords: Chimie des molécules bioatives; 5-bromo-isatin; PTC; X-Rays; 1,3-dipolar cycloaddition; DFT; Mild steel; Vasodilator effect; Antibacterial activity